Optimal Placement and Sizing of Thyristor-controlled-series-capacitor using Gravitational Search Algorithm - Purwoharjono Purwoharjono; Muhammad Abdillah; Ontoseno Penangsang; Adi Soeprijanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
This paper represents the Gravitational Search Algorithm (GSA) that can be used to determine the optimal location and rating of Thyristor controlled Series Capacitor (TCSC). TCSC is equipment used to regulate and improve power flow in power system. The method used in this study was GSA. TCSC were the implemented on 500kV Java-Bali Power System. Loadflow results before optimization using Newton Rapshon method showed that active power loss was 297.607MW. While loadflow results after optimization using GSA with 5-TCSC obtained were 287.926MW of active power loss, with 10-TCSC, it was obtained 281.143MW of active power loss. In addition, using 15-TCSC, active power loss obtained was 279.405MW. GSA methods can be used to minimize power losses and transmission lines as well as to improve value of voltage in the range of 0.95+ 1.05pu compared with loadflow results before optimization.The more TCSC is used, then value of active power losses small.